Journaling therapy for patients with social isolation - Firmansyah, Dwi Ayu Lestari; Pinilih, Sambodo Sriadi; Amin, Muhammad Khoirul (Innovation in Health for Society, 2023)
Social isolation led to multiple chronic conditions, including heart, lung, cardiovascular, hypertension, atherosclerosis, and other clinical conditions. When left untreated, social isolation causes depression, psychological stress, and anxiety. However, the use of journal therapy is scarce in the literature. Therefore, the study evaluated the benefits of journaling therapy in patients with social isolation. The finding showed that this therapy decreases the willingness to social isolation in the community setting. It is hoped that journaling therapy can be used for patients with psychological problems. Keywords: Social isolation; nursing care; community nursing; journaling therapy; mental health issue